APHRODISIAC ACTIVITY OF TRIBULUS TERRESTRIS EXTRACT IMPROVES MALE REPRODUCTIVE SYSTEM PARAMETERS AND FERTILITY - S. Malekzadeh; H. K. Jashni; F. Hooshmand (Journal of Animal and Plant Sciences, 2024)
Since Tribulus Terrestris (TT) is known as an aphrodisiac and natural muscle-enhancing nutrition, this study aimed to investigate the effects of TT on the male reproductive system, including sex hormones, testicular histology, and sperm parameters. In this study, 35 adult male Wistar rats were randomly divided into five groups of seven rats including Control, Sham (normal saline, 2.5 ml), TT1, TT2 and TT3 (2.5, 5 and 10 mg/kg body weight, respectively). One day after receiving the last TT administration (by gavage once daily for 60 days), rats were sacrificed, testes were removed, blood samples were taken from the heart, and sperm analysis was performed. Results showed that administration of TT extract was significantly increased serum hormonal levels (Testosterone, FSH in 2.5 and 10 mg/kg, respectively), sperm parameters (sperm count and motility in 5 and 10 mg/kg of TT), and histology of the testis (the mean number of Sertoli (5 and 10 mg/kg of TT), Leydig in 2.5 mg/kg of dose) in rats (p<0.05). TT extract improves reproductive system parameters and fertility in the male rats. TT may also have beneficial effects on the male reproductive system by increasing the Testosterone hormone levels, sperm motility and testis histology.
Keywords: Tribulus Terrestris; Fertility; Spermatogenesis; Sperm Motility; Testosterone